FRI0551 Characteristics of gout patients cared for by rheumatologists – results from the corrona gout registry site survey. (23rd January 2014) - Harrold, L.; Greenberg, J.; Saunders, K.; Karki, C.; Kifayeh, N.; Kremer, J.
Abstract : Background: Gout is the most common inflammatory arthritis in the US with the majority of patients cared for by primary care providers. Little is known regarding the patients seen in rheumatology practices and the care they receive. Objectives: To ascertain treatment patterns and to characterize gout patients under the care of Rheumatologists. Methods: All sites (N=121) participating in the Consortium of Rheumatology Researchers of North America Inc. (CORRONA), a US nationwide observational rheumatic disease registry, were contacted including 143 rheumatologists. Rheumatologists were asked questions regarding gout patient characteristics, treatment patterns and outcomes. Results: Seventy rheumatologists (49%) completed the self-administered questionnaires. Treatment patterns are presented in Table 1 . Even after resolution of the acute gouty symptoms, 80% of rheumatologists reported staying involved in the chronic care of their patients. Most rheumatologists (70%) reported seeing 1-5 active gout patients a month and 75% stated they cared for 1-10 asymptomatic chronic gout patients monthly. Half of rheumatologists reported that their typical gout patient had between 0-1 flares per year, while a similar proportion (49%) reported between 2-4 per year. Similarly about half stated that <10% of their patients have recurrent gout flares yearly with another 49% stating the proportion is 10-25% of patients. The vast majority of providers estimated that up to 25% of their patients have tophi. The majority of respondents (77%) indicated that > 50% of their gout patients have achieved target serum urate levels of <6 mg/dl; furthermore, the majority of respondents (71%) indicated that >50% of their gout patients with flares are able to become flare-free with treatment within one year. The proportion of patients in their practice with chronic gout refractory to conventional therapy was estimated to be up to 10% by most rheumatologists. Image/graph: Conclusions: Rheumatologists report being engaged in caring for both active and asymptomatic patients and are actively involved in chronic gout disease management using the recommended treatment approaches. Acknowledgements: Funding for this study was provided by CORRONA (study sponsor), from a development and subscription agreement/contract with Savient. Disclosure of Interest: L. Harrold Grant/research support from: National Institute of Health - K23AR053856, Consultant for: CORRONA Inc., J. Greenberg Shareholder of: CORRONA Inc., Consultant for: Astra Zeneca, CORRONA Inc., Novartis, Pfizer, K. Saunders Employee of: CORRONA Inc., C. Karki Employee of: CORRONA Inc., N. Kifayeh Employee of: CORRONA Inc., J. Kremer Shareholder of: CORRONA Inc., Employee of: CORRONA Inc.